2011
DOI: 10.4244/eijv7i4a80
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of frequency domain optical coherence tomography in pigs

Abstract: Frequency domain OCT is safe and efficacious in the porcine model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…11,12,17,18 Although FD-OCT, the newest iteration of OCT, eliminates the need for balloon occlusion with its rapid acquisition rate, blood cell clearance by use of this technique has historically required a more viscous agent (eg, iodinated contrast material) to provide effective clearance of red blood cells during periods of uninterrupted blood flow. 3,19 Previous studies of carotid OCT imaging have reported using either iodinated contrast material with FD-OCT or saline and balloon occlusion with TD-OCT to achieve satisfactory blood clearance for "diagnostic" quality images. [10][11][12][13][14] We hypothesized that the carotid vasculature would accommodate significantly higher volumes of flush media compared with the coronary arteries, allowing for effective blood clearance with saline injections during FD-OCT imaging.…”
Section: Discussionmentioning
confidence: 99%
“…11,12,17,18 Although FD-OCT, the newest iteration of OCT, eliminates the need for balloon occlusion with its rapid acquisition rate, blood cell clearance by use of this technique has historically required a more viscous agent (eg, iodinated contrast material) to provide effective clearance of red blood cells during periods of uninterrupted blood flow. 3,19 Previous studies of carotid OCT imaging have reported using either iodinated contrast material with FD-OCT or saline and balloon occlusion with TD-OCT to achieve satisfactory blood clearance for "diagnostic" quality images. [10][11][12][13][14] We hypothesized that the carotid vasculature would accommodate significantly higher volumes of flush media compared with the coronary arteries, allowing for effective blood clearance with saline injections during FD-OCT imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Most operators in the United States use undiluted contrast material. Despite concerns for reduced viscosity and image quality, there have been reports of adequate image quality with both a 50:50 combination of a crystalloid with contrast during manual injections 22 and power injection of lactated Ringers solution alone without any mixed contrast. 24 Manual or Power Injection Both manual and power injection of flushing media resulted in similar blood-free vessel lumen in the early TD-OCT studies.…”
Section: Flushing Options To Create a Blood-free Lumenmentioning
confidence: 96%
“…Iodixanol is the most viscous contrast agent and remains the one of choice. [17][18][19][20][21][22][23][24] Recently, 3 human studies have shown that the quality of image produced by FD-OCT was comparable with that produced using contrast media or lowmolecular-weight dextran L (LMD-L). 20,21,23 LMD-L may thus be an acceptable and safe alternative to contrast agents for FD-OCT, although at present only contrast media is approved by the FDA for OCT image acquisition.…”
Section: Flushing Options To Create a Blood-free Lumenmentioning
confidence: 99%
“…Animal studies directly comparing different flush solutions have consistently shown that higher viscosity solutions provide superior imaging results and in humans, high viscosity agents have been reported to achieve excellent image quality. Iodixanol (Visipaque, GE Health Care, Cork, Ireland) is the most viscous of the contrast agents and has been the contrast agent of choice in these studies . Three recent studies directly compared contrast media to low molecular weight Dextran‐40 (LMD‐L) in humans undergoing FD‐OCT and found that image quality was comparable between the two media, suggesting that although not currently FDA approved, low molecular weight Dextran may be a suitable alternative to contrast media for FD‐OCT acquisition, with an acceptable safety profile .…”
Section: Background and Introductionmentioning
confidence: 99%
“…While in the US most operators use undiluted contrast material, a combination of a crystalloid in a 50:50 mix with contrast during manual injections has also been described, although the addition of crystalloid to contrast media decreases viscosity and potentially, image quality . Nonetheless there are reports of adequate image quality even with power injection of LR solution alone, without contrast .…”
Section: Background and Introductionmentioning
confidence: 99%